Mitologi dan Rekontruksi Destinasi Wisata B29 : Studi pada Masyarakat Tengger di Desa Argorasi Kecamatan Senduro Kabupaten Lumajang - Muqit, Abdul; Munib, Muhammad (Proceedings of Annual Conference on Community Engagement, 2018)
Today tourism seems to be a phenomenon of human life that is never separated from debate and analysis especially regarding socio-economic activities. Communities and governments sometimes often forget about tourist attractions that originally had a history and then a myth emerged which the Tengger people still believed and believed in. This study speaks of myths in B29 tourist destinations which are interesting objects by expressing mythology and reconstruction as well as the response of the surrounding community, by narrating a mythology and describing events before and after becoming a B29 tourist destination. This study aims to narrate mythology and reconstruction of B29 tourist destinations by using qualitative research and narrative approaches. The results of the study that the Tengger tribe society in daily life is overwhelmed by myth. Myths about holy characters, sacred places, spirits and the like. Myth in the Tengger tribe society has its own functions and roles. So they still respect sacred objects and preserve and preserve them to date, as evidenced by the maintenance of petilasan at the peak of B29 tourism.